Pengaruh Literasi Keuangan, Financial Technology dan Locus of Control terhadap Penggunaaan Paylater kepada Mahasiswa Universitas Balikpapan - Permadi, Riza; Anggraini, Diah; Susanti, Nira Dewi; Sa’diyah, Nur; Nurlia, Nurlia (Lembaga Teewan Journal Solutions, 2026)
The development of financial technology has encouraged changes in financial behavior, especially among students as active users of digital services. One of the rapidly growing services is paylater, which offers transaction convenience through deferred payment systems. However, uncontrolled use of paylater may create personal financial risks such as consumptive behavior and debt accumulation. This study aims to analyze the influence of financial literacy, financial technology, and locus of control on the use of paylater among students at Universitas Balikpapan from a financial risk management perspective. This study uses a quantitative method with data collection techniques through questionnaires distributed to students of Universitas Balikpapan. The sampling technique used is non-probability sampling with a purposive sampling approach. Data analysis was conducted using Structural Equation Modeling based on Partial Least Square (SEM-PLS) with the assistance of SmartPLS software. The results are expected to show that financial literacy, financial technology, and locus of control significantly influence the use of paylater. This study implies that financial understanding, technological convenience, and self-control are important factors in minimizing financial risks arising from the use of digital credit services. This research is expected to serve as an evaluation material for students to be wiser in using paylater services and to increase awareness of personal financial risk management.